Sul Breviario dei politici del cardinale Giulio Mazzarino - Benedetti, Amedeo (Rivista di studi politici internazionali, 2022)
The article concerns the Breviarium politicorum of Cardinal Giulio Mazzarino. The Autor provides a pragmatic approach to Mazzarino’s fundamental book, by highlighting a few passages and comparing them with analogous statements of other great personalities of the XVII century, like Baltasar Gracián or Armand Jean du Plessis, Cardinal-Duc de Richelieu. The focus is on the aspects of Mazzarino’s work that are still valid today, among which the decisive role of imperturbability, the importance in self-promotion of knowledge, of perfectionism, of language, and of psychological observation.